The cook's garden : a gardener's guide to selecting, growing, and savoring the tastiest vegetables of each season - West, Kevin, 1970- (Alfred A. Knopf, 2025)
"For Kevin West, the surest path to a successful garden leads through the kitchen door. And preparing for a fantastic meal of home-grown vegetables-the kind of meal that leaves you not only satisfied, but grateful-is just what he wants to help you learn to do. In The Cook's Garden, West gives readers the tools and confidence they need to grow food for their own meals. From gardening basics and advice on harvesting, to delicious recipes showing how to make the best use of produce in any season-including primers on freezing surplus vegetables, making pantry staples such as canned tomatoes, and effectively using stored produce-this book promises to inspire anyone, even if their growing plot is as small as a window box in a city apartment. West's erudite yet practical guide is interwoven with meditations on the beauty, poetry, and spirituality inherent in growing and preparing one's own food. The Cook's Garden guides readers through jumpstarting their gardens and revolutionizing their kitchens-while also nourishing their minds and souls"--